Long-term grazing exclusion influences arbuscular mycorrhizal fungi and their association with vegetation in typical steppe of Inner Mongolia, China - Xue-jiao CHEN; Qi-mei LIN; Xiao-rong ZHAO; Hao CHEN; Jing WEN; Ying LI; Gui-tong LI (Journal of Integrative Agriculture, 2018)
It is not certain that long-term grazing exclusion influences arbuscular mycorrhizal (AM) fungi and their association with steppe vegetation. In this study, soil and plant samples were collected from two sites of grazing exclusion since 1983 (E83) and 1996 (E96), and one site of free-grazing (FG) in the typical steppe of Xilinguole League, Inner Mongolia, China, and assayed for soil basic physicochemical properties, AM fungal parameters, aboveground biomass and shoot phosphorus (P) uptake as well. The results showed that long-term grazing exclusion of E83 and E96 led to less drastic seasonal changes and significant increases in spore density, hyphal length density and root colonization intensity of AM fungi and even soil alkaline phosphatase activity, by up to 300, 168, 110 and 102%, respectively, compared with those of FG site. In addition, the total aboveground biomass and shoot P uptake of E83 and E96 were 75–992% and 58–645%, respectively, higher than those of FG. Generally, the root colonization intensity, spore density, and hyphal length density of AM fungi were all positively correlated with the aboveground biomass and even shoot P uptake of plant. These results may imply that grazing exclusion play a critical role in increasing the growth of AM fungi, and subsequently, may increase plant P uptake and aboveground biomass production. Moreover, the spore density could sensitively reflect the impacts of long-term grazing exclusion on AM fungi since survival strategy of spores in soil.